Topic anaesthesia with a eutectic mixture of lidocaine/prilocaine cream after elective caesarean section: a randomised, placebo-controlled trial - Große Steffen, Thomas; Krämer, Malin; Tuschy, Benjamin; Weiß, Christel; Sütterlin, Marc; Berlit, Sebastian (Archives of gynecology and obstetrics, 2017)
Purpose: Aim of the study was to investigate the topical application of a eutectic mixture of lidocaine/prilocaine (EMLA®) cream after caesarean section (CS) and its effect on postoperative pain, time to mobilisation, and time to discharge. Materials and methods: A total of 189 pregnant women were enrolled; full data sets were available for 139 of them, who were prospectively randomised to receive either placebo (control group) or EMLA® cream (study group) on the CS lesion directly as well as 24 h after surgery. Postoperative pain was assessed 24 and 48 h after surgery using the short form of the McGill Pain Questionnaire (SF-MPQ). Additional analgesic pain medication on demand was assessed in both groups. Results: A total of 62 women were allocated randomly to the study and 77 patients to the control group before primary CS. There were no statistically significant differences regarding demographic and surgical parameters comparing both collectives. In addition, the postoperative total pain scores after 24 h [McGill total: 38.5 (0-102) vs. 50 (0-120) p = 0.0889] as well as after 48 h [24 (0-79) vs. 30.5 (0-92); p = 0.1455] showed no significant differences. Furthermore, time to mobilisation (hours) [9.68 (2.18-51.38) vs. 9.47 (4.18-41.77); p = 0.5919] and time to discharge (hours) [98.6 (54.08-170.15) vs. 98.2 (43.45-195.87); p = 0.5331] were comparable. Conclusion: The postoperative application of EMLA® cream after CS did not reduce postoperative pain or time to mobilisation or discharge, so that its use in this context has to be seen critically.